Analisis Spesifikasi Kerusakan Lambung Kapal yang Melakukan Perbaikan di PT Dok dan Perkapalan Kodja Bahari Galangan II - Muhammad Irsad Syafiq; Faiz Ilham Mumtaz; Miftaah Bagus Hartawan; Siti Sahara (Peneliti.net, 2023)
This study aims to analyze the causes of ship damage that often occurs in the field and determine the factors that influence it, in addition to analyzing data on the results of ship repairs that have been carried out at PT Dok and Perkapalan Kodja Bahari Galangan 2, as well as presenting reports on accurate analysis results and objective to be used as a reference for the shipping industry and researchers who are interested in the same topic. The method used is through interviews with one of DKB Galangan II employees. The KAPRO Division and conducted a document study by collecting various documents related to the ship repair process at DKB Galangan II. The type of research used is descriptive qualitative. Based on the results of an interview with Mahruf who served as Project Head (KAPRO) for ship repair activities carried out at the shipyard of PT. Dock & Shipping Kodja Bahari Galangan II is divided into 3 types of maintenance, namely annual maintenance (light ship repair), large wharf (heavy ship repair), and emergency maintenance.